2014
DOI: 10.4161/15384101.2014.943581
|View full text |Cite
|
Sign up to set email alerts
|

Expression, regulation and function of Egr1 during implantation and decidualization in mice

Abstract: Early growth response gene 1 (Egr1), a zinc finger transcriptional factor, plays an important role in regulating cell proliferation, differentiation and angiogenesis. Current data have shown that Egr1 is involved in follicular development, ovulation, luteinization and placental angiogenesis. However, the expression, regulation and function of Egr1 in mouse uterus during embryo implantation and decidualization are poorly understood. Here we showed that Egr1 was strongly expressed in the subluminal stroma surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…In contrast, KLF13 loss did not affect Esr2 expression and preferentially diminished Pgr-b rather than Pgr-a, expression, the latter based on the comparable reductions in total Pgr and Pgr-b transcripts. The functional consequence of the distinct changes in Pgr-a vs. Pgr-b in Klf13 null vs Klf9 null lesions is convincingly illustrated by the contrasting effects elicited by Klf9 and Klf13 null mutations (relative to WT) on the expression of the same PGR target genes (Wnt1, Wnt4, Dkk1, Egr1) [37][38][39][40] and is consistent with the opposing transactivities of PGR-A and PGR-B isoforms [41]. However, since P 4 -regulated genes may also be direct or indirect E 2 -target genes (e.g.…”
Section: Dicussionmentioning
confidence: 99%
“…In contrast, KLF13 loss did not affect Esr2 expression and preferentially diminished Pgr-b rather than Pgr-a, expression, the latter based on the comparable reductions in total Pgr and Pgr-b transcripts. The functional consequence of the distinct changes in Pgr-a vs. Pgr-b in Klf13 null vs Klf9 null lesions is convincingly illustrated by the contrasting effects elicited by Klf9 and Klf13 null mutations (relative to WT) on the expression of the same PGR target genes (Wnt1, Wnt4, Dkk1, Egr1) [37][38][39][40] and is consistent with the opposing transactivities of PGR-A and PGR-B isoforms [41]. However, since P 4 -regulated genes may also be direct or indirect E 2 -target genes (e.g.…”
Section: Dicussionmentioning
confidence: 99%
“…18 As the progression of decidualization was increasing, Hmgn1 expression was gradually enhanced and reached a peak at 96 h (Fig. 4C).…”
Section: Hmgn1 Mrna Expression During Delayed Implantation and Activamentioning
confidence: 99%
“…Hybridization was performed as described previously. 18 Sections were counterstained with 1% methyl green. The positive signal was visualized as a dark brown color.…”
Section: Steroid Hormonal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In the reproductive system, it has been reported that knockout of EGR1 can lead to female infertility through its regulation of LH-b transcription in mice, 18 and EGR1 may be essential for embryo implantation and decidualization in mice. 19 However, there is no direct evidence that EGR1 participates in GC apoptosis and follicle atresia during ovarian aging. The aims of this study were to investigate the expression manner of EGR1 in the mouse ovary and to explore the EGR1 regulated signaling pathway involved in GC apoptosis.…”
Section: Introductionmentioning
confidence: 99%